THE EFFECT LEG MUSCLE EXPLOSIVE POWER, FLEXIBILITY, HAND EYE COORDINATION AND CONFIDENCE OF SKILL LAY UP SHOOT BASKETBALL - Oki Candra; Moch. Asmawi; James Tangkudung (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
The purpose of this research is to obtain information on the direct and indirect influence of leg muscle explosive power, flexibility, hand eye coordination and self confidence in basket lay up shoot skills. The research method used in this research is the type of quantitative research with correlational study approach. Technical analysis using path analysis approach (path analysis). The total population of this research is 41 students, sampling technique by total sampling. Total samples in this research is 41 students who followed extracurricular. The results of this research concluded: (1) leg muscle explosive power directly affect the skills of lay up shoot as 0.408, (2) flexibility direct influence on skills lay up shoot as 0.297, 3) hand eye coordination directly affect the skills of lay up shoot as 0,217, (4) self confidence directly influence to skill of lay up shoot as 0,151, (5) leg muscle explosive power directly influence to self confidence as 0,317, (6) flexibility direct influence to self confident as 0,261, 7) hand eye coordination has a direct effect self confidence as 0.282. Keywords: leg muscle explosive power, flexibility, hand-eye coordination confidence, lay up shoot, survey